2017
DOI: 10.1051/sicotj/2017034
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted navigation in total knee and hip arthroplasty

Abstract: Introduction: Computer assisted surgery was pioneered in early 1990s. The first computer assisted surgery (CAS) total knee replacement with an imageless system was carried out in 1997. In the past 25 years, CAS has progressed from experimental in vitro studies to established in vivo surgical procedures. Methods: A comprehensive body of evidence establishing the advantages of computer assisted surgery in knee and hip arthroplasty is available. Established benefits have been demonstrated including its role as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 50 publications
1
54
1
Order By: Relevance
“…These findings are consistent with two other studies, 44,45 though they could not be included in our pooled analysis because risk estimates for dislocation risk were not available. Though computer-assisted surgical techniques improve cup position in THR surgery 46 and are increasingly being adopted by surgeons, 47 little evidence exists to show they actually improve outcomes and reduce complication rates in total joint replacement. 44,45,48,49 In the United States, it has been estimated that there will be an increase in the demand of primary THRs by 174% between 2005 and 2030.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with two other studies, 44,45 though they could not be included in our pooled analysis because risk estimates for dislocation risk were not available. Though computer-assisted surgical techniques improve cup position in THR surgery 46 and are increasingly being adopted by surgeons, 47 little evidence exists to show they actually improve outcomes and reduce complication rates in total joint replacement. 44,45,48,49 In the United States, it has been estimated that there will be an increase in the demand of primary THRs by 174% between 2005 and 2030.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the research results showed that constructive systematic nursing measures have significantly different effects on pain intensity after TKA. The literature indicated that patients who undergo computer-navigated surgery do not suffer from a serious loss of blood or pain because intramedullary nailing of the femur is not required for CAS-TKA [15]. The findings showed that the use of CPM devices can relieve pain intensity after surgery and that it is an appropriate rehabilitation exercise for alleviating pain.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the research results showed that constructive systematic nursing measures have signi cantly different effects on pain intensity after TKA. The literature indicated that patients who undergo computer-navigated surgery do not suffer from a serious loss of blood or pain because intramedullary nailing of the femur is not required for CAS-TKA [27]. The ndings showed that the use of CPM devices can relieve pain intensity after surgery and that it is an appropriate rehabilitation exercise for alleviating pain.…”
Section: Discussionmentioning
confidence: 99%